Risk Mapping of Bogie S2HD-9C Production Process that Take Effect on Production Fulfillment at PT. Barata Indonesia (Persero) - Faza Yoshio Susanto; Naning Aranti Wessiani (Direktorat Riset dan Pengabdian Masyarakat (DRPM), ITS, 2016)
PT Barata Indonesia (Persero) is one of leading metal works company in Indonesia. It has 3 main business line which are engineering procurement and construction (EPC), industrial tools manufacturing, and foundry. As the company’s strategic objective in delivering quality product and service to the customer, PT Barata Indonesia should maintain their production process properly. One of the featured product of PT Barata Indonesia is bogie. The production process of bogie shows a fluctuative delivery fulfillment. It can be proved by the contract amendment information. Risk management can be used as the method to manage risk inside the production process of bogie. Therefore, this research is aimed to identify risks that may occur from each activities of bogie S2HD-9C’s production process. The risk identification is done by using fault tree analysis method in order to determine the root cause of each activity performed. The risk evaluation is done by using FMEA method which can classify the effects of failure based on the severity and occurrence of failure. Then continue to the risk mapping and risk mitigation determination for bogie S2HD-9C’s production process. Loss that caused by the emergence of risk also determined using value at risk method. Moreover, risk profile dashboard will be provided as the tools in managing risk.